Faktor Penentu Produktivitas Tenaga Panen di Perkebunan Kelapa Sawit (Elaeis guineensis) PT Danar Rimba Raya - Prasetiyo, Joko Widodo Budi; Karim, Akhmad Rizqul; Putri, Dindi Darmawati (Perkebunan dan Lahan Tropika, 2026)
Determinant Factors of Harvest Labor Productivity in Oil Palm (Elaeis guineensis) Plantation at PT Danar Rimba Raya. Oil palm plantations play a strategic role in Indonesia’s economy by contributing significantly to export earnings and rural employment. However, productivity challenges in labor-intensive harvesting activities remain a critical issue affecting production efficiency and sustainability. This study aims to analyze the productivity of harvest workers and identify the factors influencing it at PT Danar Rimba Raya Pelantaran Estate, Kotawaringin Timur Regency, Central Kalimantan. In 2024, the company’s production realization reached only 80% of the target, with a worker attendance rate of 90%. A descriptive quantitative approach was employed using a census method involving 24 harvest workers. Data were collected through questionnaires, field observations, and interviews, and analyzed using multiple linear regression. The results show an adjusted R² value of 0.958, indicating that 95.8% of productivity variation was explained by the model. Partial test results revealed that work experience had a significant negative effect (β = –0.217; p < 0.05), while incentives had the strongest positive influence on productivity (β = 0.632; p < 0.01). Other variables, including age, motivation, tool availability, and work environment, were not statistically significant. These findings emphasize the importance of performance-based incentive systems and adaptive labor management strategies to enhance productivity in the oil palm plantation sector.